The relationship between organizational support and job satisfaction of experts and managers of Islamic Azad University of Qeshm and subsidiaries (international units, medical, Sama, Hormuz and Khamir) - Maryam Rasooli; Mahnoosh Abedini (Dutch Journal of Finance and Management, 2017)
This study was conducted to investigate the relationship between organizational support and job satisfaction of experts and managers of Islamic Azad University of Qeshm and subsidiaries (international units, medical, Sama, Hormuz & Khamir). The study was descriptive and correlational research. The statistical population was 90 individuals of experts (70) and managers (20), who were selected by simple random sampling. Research tools include job satisfaction and perceived organizational support questionnaires. Cronbach's alpha coefficient was used to examine the reliability of questionnaires. The results showed that all instruments have good reliability for use in this research. Data analysis showed that there was a significant and positive relationship between organizational support and job satisfaction. Regression analysis indicated that organizational support was able to predict 40 percent of job satisfaction of Islamic Azad University of Qeshm and subsidiaries. Also, perceived organizational support of experts was more than managers.
Keywords: 650; organizational support; job satisfaction; Islamic Azad University